Environmentally stable, mechanically flexible, self-adhesive, and electrically conductive Ti3C2TX MXene hydrogels for wide-temperature strain sensing. (December 2021) - Li, Shi-Neng; Yu, Zhi-Ran; Guo, Bi-Fan; Guo, Kun-Yu; Li, Yang; Gong, Li-Xiu; Zhao, Li; Bae, Joonho; Tang, Long-Cheng
Abstract: Conductive hydrogels are promising in the flexible wearable electronic applications due to their unique feature of intrinsic stretchability, reversible flexibility, and high electrical conductivity. However, severely poor adaptability under cold or hot environmental conditions along with inferior adhesiveness to various substrates greatly hinders the potential applications in such emerging field. Herein, we describe a mechanically flexible and electrically conductive nanocomposite hydrogel composed of polyacrylamide-co-acrylic acid/chitosan covalent-network reinforced by Ti3 C2 Tx MXene nanosheets within water-glycerol binary solvent via a simple one-pot free radical polymerization. Notably, incorporation of a low content (0.1–0.3 wt%) of MXene promotes the rapid gelation of the polymer molecules in only 10 min. The optimized hydrogel containing 0.2 wt% MXene not only possesses excellent mechanical performance (e.g., tensile elongation of ~1000%) and improved electrical conductivity (~1.34 S/m), but also shows stable temperature tolerance from − 20 to 80 °C and self-adhesion with various substrates (e.g., steel, glass, rubber, plastics and skin) as well as a rapid self-healable feature (~1.3 s). Further, such hybrid MXene hydrogel exhibits dual sensations under different strain (1–600%) and stress (80–3200 Pa) ranges, good applicability for various deformation conditions (tension/bend/compression), and wide temperature adoptability with stable repeatability. Clearly, this versatile MXene nanocomposite hydrogel developed may provide a new route for the rational design and development of advanced skin-like sensor for complex environmental application. Graphical Abstract: ga1 Environmentally stable, mechanically flexible, self-adhesive, and electrically conductive Ti3 C2 TX MXene hydrogels were fabricated through a facile one-pot free radical polymerization approach; and the optimized hydrogels possessed excellent mechanical performance (e.g., tensile elongation of ~1000%) and improved electrical conductivity (~1.34 S/m), but also shows stable temperature tolerance from − 20 to 80 °C and self-adhesion with various substrates (e.g., steel, glass, rubber, plastics and skin) as well as a rapid self-healable feature (~1.3 s), showing promising for wide-temperature strain sensing applications. Highlights: MXene-based multifactional hydrogels are fabricated by a one-pot polymerization strategy. The optimized hydrogels show excellent mechanical flexibility and self-adhesive performance. Outstanding temperature tolerance and a rapid healable feature of the hydrogel are obtained. Such MXene strain sensor exhibits good reliability and adoptability in complex environments.